"sexy" and "laddish" girls - Dobson, Amy (2014)
Unpacking ideologies at work within contemporary popular media discourses about young womanhood can be challenging when the terrain of their representation is often presented in a kind of binary-oppositional fashion. There is concern that in contemporary popular culture traditional gender roles are becoming even more entrenched, with femininity increasingly defined around notions of (hyper, hetero-normative) "sexiness." At the same time, it seems that certain aspects of masculinity, namely sexual hedonism and social, drinking-centred hedonism, have conditionally opened up to young women. The panics that exist around both the figures of the "sexy girl" and the "laddish girl" lead me to unpack here how it is that concerns about women's excessive "sexiness," and the gendered reinforcement of the sex-object role, relate to discourses of gender "transgression" that often circulate around the figure of the "ladette," and the supposedly new-found freedoms she is exercising. I suggest that while the figures of the "sexy girl" and the "laddish girl" are both to some extent deplored and constructed as "excessive" and "transgressive" in recent media discourses, they are also both normalised and publicly imag(in)ed through such discourses as central post-feminist paradigms of young womanhood. I go on to explore a possible ideological function of the co-existence of "sexy" and "laddish" girls as normative figures within contemporary media culture. © 2014 Taylor and Francis.